Identification of a de novo splicing variant in the Coffin–Siris gene, SMARCE1, in a patient with Angelman‐like syndrome. Issue 1 (11th December 2018) - Aguilera, Cinthia; Gabau, Elisabeth; Laurie, Steve; Baena, Neus; Derdak, Sophia; Capdevila, Núria; Ramirez, Ariadna; Delgadillo, Veronica; García‐Catalan, Maria Jesus; Brun, Carme; Guitart, Miriam; Ruiz, Anna
Abstract: Background: Patients affected by Angelman syndrome (AS) present severe intellectual disability, lack of speech, ataxia, seizures, abnormal electroencephalography (EEG), and a characteristic behavioral phenotype. Around 10% of patients with a clinical diagnosis of AS (AS‐like) do not have an identifiable molecular defect. Some of these patients harbor alternative genetic defects that present overlapping features with AS. Methods: Trio whole‐exome sequence was performed on patient and parent's DNA extracted from peripheral blood. Exome data were filtered according to a de novo autosomal dominant inheritance. cDNA analysis was carried out to assess the effect of the splice site variant. Results: We identified a novel heterozygous SMARCE1 splicing variant that leads to an exon skipping in a patient with an Angelman‐like phenotype. Missense variants in the SMARCE1 gene are known to cause Coffin–Siris syndrome (CSS), which is a rare congenital syndrome. Clinical reevaluation of the patient confirmed the presence of characteristic clinical features of CSS, many of them overlapping with AS. Conclusions: Taking into account the novel finding reported in this study, we consider that CSS should be added to the expanding list of differential diagnoses for AS. Abstract : We identified with trio exome sequencing, a novel heterozygous SMARCE1 splicing variant that leads to an exon skipping in a patient with an Angelman‐like phenotype.